Video game use, acceptance, and relationship experiences: a moderated actor-partner interdependence model - Norton, A; Brown, CC; Falbo, R; Hogan, B (Mary Ann Liebert, 2020)
With video game use widely accepted and practiced in a wide variety of households worldwide, it is important for researchers to understand links between video game use and romantic relational experiences. Although unexplored within gaming literature, previous research has indicated the importance of attitudes of acceptance or approval within the couple relationship with acceptance of a partner's specific behavior being linked to relational outcomes. Using dyadic data from 6,756 couples (n = 13,512) from 16 different countries, an actor-partner interdependence moderating model was employed to evaluate how acceptance of video game use moderated the link between video game use and dyadic adjustment, while controlling for mental health, relational characteristics, and other demographic variables. Results indicate that higher reports of individual video game use were linked with improved rates of partner dyadic adjustment. Furthermore, results indicated that partner-interaction effects for acceptance of video game use moderated the relationships between video game use and dyadic adjustment. This supports the importance of considering contextual factors when examining gaming use and its links with other constructs.